Surrogate Motherhood: Analysis of the Basis of the Legislation of Ukraine and Foreign Countries - VASILIEVA, Valentina A.; STEFANYSHYN, Natalia M.; SKHAB-BUCHYNSKA, Tetiana Ya. (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018, 2019)
In modern conditions, the use of methods of additional reproductive technologies is becoming increasingly relevant, which justifies the need for proper legal regulation of relevant legal relationships. A detailed study of diverse national approaches to solving the problem of surrogate motherhood shows the ambiguity of the position of legislators. Therefore, a comparative analysis of the foundations of legislation in this area gains a special significance within the framework of legal science.The objective of the article is to analyze the essence and content of the institute of surrogate motherhood, evaluate the current legislation of Ukraine in the specified area and conduct comparative analysis with the legislation of other states, elaborate recommendations and outline the prospects for further development of the domestic legal regulation of the studied legal relations.According to the results of the research, the authors define the concept of ‘contract of surrogate motherhood’ and proposes the adoption of a scientifically and legally substantiated Concept of Legal Acknowledgement of the Institute of Surrogate Motherhood, within the framework of which there should be a single normative legal act – the Law of Ukraine ‘On Surrogate Motherhood’ with simultaneous amendments to the current legislation of our country.